2016
DOI: 10.1177/1060028016655179
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pediatric Type 2 Diabetes

Abstract: Metformin and insulin remain the mainstay of treatment for T2DM in pediatric patients. More robust studies are needed to assist in the provision of evidence-based guidance for the treatment of T2DM in youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
0
11
0
2
Order By: Relevance
“…This increase in Sertoli cell number leads to a duplication of testicular volume from 2 to 4 mL, clinically reflected in Tanner stage 2 (Rey et al 2016). At this point, it is important to remind that the incidence of both T2D and obesity in children has risen at staggering rates and that MET has started to be used in pediatric population at the time when Sertoli cells are proliferating (Brufani et al 2013, Adeyemo et al 2015, Smith et al 2016. If MET alters postnatal Sertoli cell proliferation in mammalian testis, it should be considered a warning about possible deleterious effects on future fertility when this drug is used in children.…”
Section: Introductionmentioning
confidence: 99%
“…This increase in Sertoli cell number leads to a duplication of testicular volume from 2 to 4 mL, clinically reflected in Tanner stage 2 (Rey et al 2016). At this point, it is important to remind that the incidence of both T2D and obesity in children has risen at staggering rates and that MET has started to be used in pediatric population at the time when Sertoli cells are proliferating (Brufani et al 2013, Adeyemo et al 2015, Smith et al 2016. If MET alters postnatal Sertoli cell proliferation in mammalian testis, it should be considered a warning about possible deleterious effects on future fertility when this drug is used in children.…”
Section: Introductionmentioning
confidence: 99%
“…Elle permet de réduire le taux d'HbA1c de 1 % à 2 %, n'entraînant que des effets secondaires minimes (p. ex. nausée, diarrhée) ; elle ne provoque pas d'hypoglycémie puisqu'elle augmente la sensibilité à l'insuline et n'agit donc pas sur la production d'insuline [49] . Un autre agent, le glimépiride, apporte une réduction comparable de l'HbA1c chez l'adolescent, mais est associé à une prise pondérale.…”
Section: Prise En Charge Complémentaireà L'alimentation Et Aux Habituunclassified
“…Insulin and metformin are the only two FDA-approved medications for diabetes in patients younger than 18 years old, but other medications such as thiazolidindiones and incretins have been used with success as off-label agents in some patients(7, 23). The TODAY study (7) demonstrated that the addition of rosiglitazone enhances the efficacy of metformin, improving rates of glycemic control.…”
Section: Nonsurgical Treatment Options For T2dmentioning
confidence: 99%